Konflik Supporter Jakmania Dan Maung Bandung Ditinjau Dari Komunikasi Lintas Budaya - Hiswanti, Hiswanti; M., Herna; Hidayaturahmi, Hidayaturahmi (representamen, 2020)
The incident between supporters of Jakmania and Maung Bandung which led to an endless conflict and various efforts have been tried to minimize the feud between supporters of this football club. Observing cross-cultural communication, differences in the background of values, artifacts, and language are often sources of conflict and this has happened to both Jakmania and Maung supporters in Bandung. Jakmania and Maung Bandung conflict management can be approached including encouraging collaborative relations and mutual respect, empowering individuals, groups, and communities to find positive resources for humane and constructive change, generating and using positive resources for the good of the overall system, building community awareness and systemic on the part of the participants, helping the group to jointly build a positive future. The conflict resolution approach is carried out within the framework of alternative solutions to the resolution of Alternative Dispute Resolution (ADR) and the style of handling conflicts to accommodate / give, divert attention from conflict, compromise / give and take, collaboration / work together to find solutions for Jakmania and Maung Bandung. Keywords: Cross Cultural Communication, Conflict, Conflict Management